Optimization of process variables for esterification of bio-oil model compounds by a heteropolyacid catalyst - Prapaporn Prasertpong; Chawannat Jaroenkhasemmeesuk; John R. Regalbuto; Jeremiah Lipp; Nakorn Tippayawong (Energy Reports, 2020)
In this work, the catalytic upgrading of a bio-oil model compound via esterification with ethanol was studied using 12-tungstosilicic acid as the catalyst. The response surface method was used to investigate and optimize the process variables, which include the ethanol to acid molar ratio, catalyst loading, reaction temperature, and reaction time for maximum conversion of the organic acid for esterification under atmospheric conditions. The effect of high He pressure on acid conversion for esterification was also studied. The maximum acid conversion was almost 90%, which can be achieved at reaction temperature of 77 °C, ethanol to acid molar ratio of 5:1, catalyst loading of 4.0% w/w, and reaction time of 8.3 h. Pressurizing the reaction with inert He did not have any effect for acid conversion at this optimum condition and had a slight negative effect under the studied conditions. After upgrading, the esterified products were found to improve the heating value from 17.6 to 23.2 MJ/kg and appeared to enhance fuel properties.
Keywords: 330; Biomass; Catalytic upgrading; Design of experiments; Pyrolysis oil; Renewable energy